Using the Body Tech device with some physical exercises for aortic pain syndrome, it affects the range of motion and spinal deviation - Sajjad Muhammad Hassan; Kamel Shanin Manahi; Zainab Abdullah Mahmoud (دراسات وبحوث التربية الرياضية, 2025)
The importance of research into using the Body Tech electrical stimulation device with physical exercises lies in getting rid of spasms occurring in some trunk muscles, as well as alleviating the pain occurring in this injury. The research aimed to use the body trainer and physical exercises to treat aortic pain syndrome and assess their effect on the range of motion and spinal deviation. The researcher employed an experimental approach with a single-group design, and the research sample consisted of players with aortic pain syndrome. A rehabilitation program was then developed for them. The most important conclusions were: The results showed that the use of the electrical stimulation device (Body Tech) led to a reduction in the pain associated with the injury and thus an increase in the range of motion in the shoulder joint. It was recommended: It is necessary to prepare the muscles of the trunk and both sides so that there is no deviation in the vertebrae of the spine. Evaluate the imbalance in the strength of the muscles of the sides of the trunk